Arab Islamic voices, agencies, and abilities : disability portrayals in Muslim world literature and culture - Ben Zahra, Saloua Ali (Lexington Books, 2018)
This book explores portrayals of the disabled in Arab/Muslim post-colonial North African and Middle Eastern societies in genres ranging from classical Arabic scripture to secular popular culture. Arab/Muslim characters in Arab, Islamic, Islamist, Francophone, and global societies are explored.